Smart Initiatives to Drive Solar Energy Investments under Environmental Uncertainty: Exploring Linear and Quadratic Relationships - Sam, Aloysius; Appiah, Michael Karikari; Ameko, Elikplim; Bonsu, Beverly Akomea (International Journal of Energy Economics and Policy, 2024)
Solar energy is an environmentally friendly and reliable source of electricity and contributes immensely towards achieving Sustainable Development Goal (SDG) 7. The quantity of solar radiation reaching the earth’s surface offers enough prospects for solar and green energy investments. This study aims to develop an integrated model to explain the effects of sustainability-enabled initiatives on sustainable investment adoption and solar energy investment and to ascertain whether the relationship between solar energy investment and environmental uncertainty is parabolic (quadratic) or linear. Cross-sectional survey data from private companies in Ghana has been used. SMART-PLS version 3.3.9 has been used to analyse and confirm our hypotheses. The results showed that sustainability initiatives (e.g., supply chain integration, institutionalization, supply chain resilience, innovativeness, climate literacy, and justice) were found to be linear. Moreover, sustainable investment adoption moderates the relationships between various factors identified and solar energy investment. Again, environmental uncertainty confirmed a quadratic relationship with solar energy investment. By implications, this paper is the first of its kind to uniquely apply quadratic analysis in the context of renewable energy investment and sustainable energy in Ghana. The newly developed integrated model could be used to explain the drivers of sustainable investment adoption and solar energy investment in Ghana and beyond. Besides, the results will stimulate and re-enforce Ghana’s renewable energy policies (Act 832 and Act 1045) towards the realisation of SDGs 7 and 13.